Evaluation of construction waste in building site in Petrolina-PE - Nunes, Sarah Monteiro; Santos, Vivianni Marques Leite dos; Santos Júnior, José Edilson dos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The civil construction industry is among the economic activities that more degrade the environment, generating waste civil construction responsible for various environmental impacts. The disposal of that waste has been mainly to landfills or dumps. Due to environmental regulations, companies have to adapt as the need for environmental conservation. Based on this situation, this study aimed to conduct qualitative diagnosis of waste generation in building site of the construction of residential apartments with ground floor plus three floors and then propose mitigation measures to promote environmental quality. The local under study is located in the city of Petrolina / PE. For to conduct this research, it was realized an exploratory research in order to combine the methodological and theoretical elements, and survey information was also done through visits and a questionnaire to the person responsible for the work. It was found that waste disposal is done in an unplanned way, no wasted water and the wood’s waste is the only waste reused on site, with the remaining components of RCC placed in bucket to await collection by an outsourced company. Among the proposed improvements it was suggested the deployment of the a management system and use of the PDCA cycle (Plan-Do-Check-Act).